Check-rein technique for Achilles tendon elongation following conservative management for acute Achilles tendon ruptures: a two-year prospective clinical study - Nicola Maffulli (BMC, 2021)
Abstract Background Following conservative management for acute Achilles tendon (AT) ruptures, the tendon may heal in continuity, and some patients may present with an elongated Achilles tendon–gastrosoleus complex. This study investigated the efficacy and feasibility of a novel minimally invasive technique, which we named “check-rein procedure”, in patients with intact and elongated AT following conservative management for AT ruptures. Methods All patients who underwent the check-rein procedure for elongation of the gastrosoleus–AT complex by one experienced surgeon were prospectively enrolled. The AT resting angle (ATRA) and AT rupture score (ATRS) were assessed at baseline and repeated at 2-year follow-up, as were calf circumference and isometric plantarflexion strength of both ankles. Results Forty-three patients (43 procedures) were analysed. The mean time elapsed from injury to surgery was 28.7 ± 7.9 weeks. The mean age at surgery was 38.5 ± 5.7 years. At the last follow-up, ATRS, ATRA, isometric strength difference, and calf circumference of the affected side were increased (P < 0.0001). The rate of the return to sport was 98% (42 of 43). No wound complications or rupture were experienced by any patient. Conclusion The check-rein technique for AT elongation after conservative management of AT tears is effective and feasible to restore tendon length and calf function. The surgical outcome was influenced by the preoperative performance status, and longer time elapsed from injury to surgery worsens the outcomes.